2020
DOI: 10.1371/journal.pone.0234400
|View full text |Cite
|
Sign up to set email alerts
|

Combine performance, draft position and playing position are poor predictors of player career outcomes in the Australian Football League

Abstract: Physical testing-based draft combines are undertaken across various sporting codes to inform talent selection. To determine the explanatory power of the Australian football league (AFL) draft combine, participants drafted between 1999-2016 (n = 1488) were assessed. Testing performance, draft selection order and playing position, AFL matches played, AFL player ranking points and AFL player rating points were collected as career outcomes. Boosted regression tree analysis revealed that position and draft selectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 30 publications
0
15
1
Order By: Relevance
“…In addition, although score difference has not been previously considered by women's AF research, a study of match margin in the AFL found that a greater winning margin increases players' effective skill involvements and reduces their defensive pressure on opponents (23). As such, the present finding supports the use of the ranking points algorithm by Champion Data for the AFLW; however, it should be noted that the construct validity of ranking points has not yet been verified for either the AFL or AFLW (13).…”
Section: Discussioncontrasting
confidence: 48%
“…In addition, although score difference has not been previously considered by women's AF research, a study of match margin in the AFL found that a greater winning margin increases players' effective skill involvements and reduces their defensive pressure on opponents (23). As such, the present finding supports the use of the ranking points algorithm by Champion Data for the AFLW; however, it should be noted that the construct validity of ranking points has not yet been verified for either the AFL or AFLW (13).…”
Section: Discussioncontrasting
confidence: 48%
“…However, unidimensional assessment models are weak predictors of team selection and match performance. Gogos et al (2020) investigated 1,488 drafted players between 1999 and 2016. They found physical and anthropometric testing results could only explain 4% of matches played and 3% of in-game performance measures with individual combine tests only explaining <2% of the matches played.…”
Section: Talent Identification In Australian Footballmentioning
confidence: 99%
“…Each of the second-tier leagues and their specific inclusion within the study are presented in Table 1. The CD ranking points were utilised as the objective measure of player performance in this study due to its availability across each of the eleven leagues/competitions, as well as its previous use in the AF notational literature (Gogos, Larkin, Haycraft, Collier, & Robertson, 2020;Hiscock, Dawson, Phillips, Mitchell, & Barake, 2016;Sullivan, Kempton, Ward, & Coutts, 2020). The CD ranking points are produced by statistics provider CD (Champion Data Pty Ltd., Melbourne, Australia), and measure a player's performance by awarding players a fixed value for specific performance actions.…”
Section: Datamentioning
confidence: 99%